Why do consumers buy impulsively during live streaming? A deep learning-based dual-stage SEM-ANN analysis - Yogesh Dwivedi (Journal of Business Research, 2022)
The power of livestreaming commerce to rake in billions of revenues within hours has thrust this nascent commercial model into the global spotlight; that said, despite the prevalence of impulsive buying in livestreaming commerce, the existing knowledge regarding the phenomenon remains relatively scarce. This research seeks to unravel the critical determinants that influence consumers’ impulsive buying in livestreaming. Grounded in the Stimulus-Organism-Response paradigm, a framework is proposed to elucidate the underlying mechanism on how parasocial interaction, social contagion, vicarious experience, scarcity persuasion, and price perception translate into impulsive buying urge and behaviour in livestreaming commerce via the cognitive-affective processing system. A self-administered online questionnaire survey was conducted with 295 respondents. The data collected was validated empirically through a multi-analytical hybrid structural equation modelling-artificial neural network (SEM-ANN) technique. The results reveal that parasocial interaction, vicarious experience, scarcity persuasion, and price perception can drive cognitive and affective reactions, which in turn, induce impulsive buying urge, subject to the boundary condition of impulsive buying tendency. In sum, the findings have drawn some insightful theoretical and practical implications that can facilitate the advancement of livestreaming commerce in the modern business arena.